Spatiotemporal distribution patterns and assembly mechanisms of eukaryotic plankton communities in Liujiaxia Reservoir at the northeastern edge of the Tibetan Plateau - Lingyun Chen; Jihua Cheng; Yangcuo Wanma; Shiying Zhu; Alan Warren; Yingzhi Ning (Microbiology Spectrum)
ABSTRACT Eukaryotic plankton are important parts of the aquatic ecosystem and their community composition and spatiotemporal distribution patterns are affected by environmental factors. The Liujiaxia Reservoir is located at the northeastern edge of the Tibetan Plateau and is a vital resource for communities and agriculture in the region. Revealing the plankton diversity and their correlation with environmental factors is essential for understanding the ecological processes and mechanisms by which plankton contribute to, and maintain the ecosystem function of, the Liujiaxia Reservoir and beyond. This study investigated the detailed spatiotemporal distribution patterns and assembly mechanisms of eukaryotic plankton communities in Liujiaxia Reservoir for three periods during 2021. Significant spatial and temporal variations of abundance and community distribution of eukaryotic plankton were demonstrated. In addition, environmental factors such as water transparency, total phosphorus, total nitrogen, ammonia nitrogen, and pH were confirmed to have the most significant impact on the distribution of these communities in the reservoir. The dominant eukaryotic plankton group was Pyrrophyta, and the species interactions were predominantly cooperative. The trophic level index indicated excellent overall water quality in the reservoir. Deterministic processes were demonstrated as the predominant factors governing the assembly of eukaryotic plankton communities. This study provides valuable insight into the eukaryotic plankton community structure in the Liujiaxia Reservoir and reveals the complex relationships between plankton communities, environmental factors, and water quality.IMPORTANCEBased on 18S rDNA high-throughput sequencing, the spatiotemporal distribution patterns and assembly mechanisms of eukaryotic plankton communities were investigated. This study provides valuable insight into the eukaryotic plankton community structure in the Liujiaxia Reservoir in the northeastern edge of the Tibetan Plateau, and the relationships between eukaryotic plankton communities, environmental factors, and water quality. Through the dynamic changes of these communities, the water quality of the reservoir was assessed to provide basic data for the protection of its biodiversity. The findings of the present study will help to improve knowledge and understanding of the ecological processes and mechanisms by which plankton contribute to ecosystem function in the Liujiaxia Reservoir and beyond.